OPTIMALISASI KEMAMPUAN BERPIKIR REFLEKTIF MATEMATIS SISWA MTs MELALUI MODEL PEMBELAJARAN ICARE - Muhammad Arfan; Abdul Muin; Ramdani Miftah (ALGORITMA: Journal of Mathematics Education, 2026)
Mathematical reflective thinking is an essential competency that should be developed among students, yet its achievement remains suboptimal. This study aims to examine the effect of the ICARE learning model on students’ reflective thinking in mathematics. A quantitative approach with a quasi-experimental design and a randomized post-test-only control group design was employed. The participants were 54 students from an Islamic junior high school (MTs) in Bogor Regency, with 26 assigned to the experimental group (ICARE learning model) and 28 to the control group (conventional instruction). Data were collected through a mathematical reflective thinking test and analyzed using an independent-samples t-test. The results indicate that students taught using the ICARE learning model demonstrated significantly higher reflective thinking in mathematics than those receiving conventional instruction. Although both groups achieved moderate average scores, the experimental group outperformed the control group on all reflective thinking indicators. Furthermore, an eta squared value of 0.495 indicates a large effect, showing that the ICARE learning model has a strong effect and is effective in enhancing students’ reflective thinking in mathematics. Abstrak Kemampuan berpikir reflektif matematis merupakan kompetensi penting yang perlu dikembangkan, namun masih belum optimal pada banyak siswa. Penelitian ini bertujuan menganalisis pengaruh model pembelajaran ICARE terhadap kemampuan berpikir reflektif matematis siswa. Penelitian menggunakan metode kuantitatif dengan desain quasi-experimental dan randomized post-test only control group design. Partisipan terdiri atas 54 siswa MTs Negeri di Kabupaten Bogor, dengan 26 siswa pada kelas eksperimen (model ICARE) dan 28 siswa pada kelas kontrol (pembelajaran konvensional). Data dikumpulkan melalui tes kemampuan berpikir reflektif matematis dan dianalisis menggunakan uji-t. Hasil penelitian menunjukkan bahwa siswa yang belajar dengan model ICARE memiliki kemampuan berpikir reflektif matematis yang lebih tinggi dibandingkan siswa pada pembelajaran konvensional. Meskipun rata-rata kedua kelompok berada pada kategori sedang, seluruh indikator kemampuan menunjukkan hasil yang lebih baik pada kelas ICARE. Nilai Eta Squared sebesar 0,495 mengindikasikan bahwa model ICARE memberikan pengaruh besar terhadap kemampuan berpikir reflektif matematis siswa.